MiR-26a-5p exerts its influence by targeting EP300, a molecule known for its role in activating the PI3K/AKT/mTOR signaling pathway in CD8+tumor-infiltrating lymphocytes of colorectal cancer: miR-26a-5p targets EP300 in colorectal cancer lymphocytes - Wang, Chao; Lin, Haonan; Zhao, Wangqiang; Liang, Yixuan; Chen, Yao; Wang, Changmiao (Cellular and Molecular Biology, 2023)
Surgical resection remains the primary approach for treating colorectal cancer, which is among the prevalent types of cancers affecting the digestive system. Tumor-infiltrating lymphocyte (TIL) therapy has emerged as a prominent area of study in the field of tumor immunotherapy in recent times, with the potential to serve as a supplementary treatment for colorectal cancer. For this investigation, we employed single-cell sequencing data to assess the manifestation extent of miR-26a-5p exists in healthy colon tissue, tissue affected by colorectal cancer, and tissue adjacent to the tumor. According to our findings, tumor-infiltrating T lymphocytes express comparatively less miR-26a-5p in comparison to normal T lymphocytes, the role of it in modulating the function of tumor-infiltrating T lymphocytes is suggested. Studies on miR-26a-5p's involvement in tumor-infiltrating T lymphocytes is limited, despite previous evidence indicating its ability to facilitate the development and advancement of cancerous cells. As a result of our experiments, we concluded that miR-26a-5p hindered the PI3K/AKT/mTOR(PAM) signaling pathway, reducing the ability of CD8+ tumor-infiltrating cells eradicate tumors. Using bioinformatics tools, we utilized prediction methods to identify EP300 as the specific gene targeted by miR-26a-5p. Subsequent research understood that downregulation of EP300 counteracted the suppressive impact exerted by miR-26a-5p on the stimulation of PAM signaling pathway, while it also diminishes the viability and cytotoxicity of CD8+ tumor-infiltrating lymphocytes. Therefore, miR-26a-5p emerges as a compelling option for the effective control of TIL therapy.